An Ethics Framework for Medical Assistance in Dying: Supporting Ethical Decision-Making in the Practice of MAiD - Frolic, Andrea N. (Bioethics, 2026)
This paper presents an Ethics Framework for MAiD (Medical Assistance in Dying) to support the integration of evidence-informed, values-based, inclusive and transparent ethical decision-making into everyday MAiD practice. As with other areas of clinical practice, ethical decision-making is an intrinsic part of MAiD. While clinicians connected to academic medical centers or large hospitals may have access to the expertise of an ethicist, those working independently, or in community-based, rural or remote settings may wrestle with ethical issues alone. Without a process to guide ethical reflection and analysis, clinicians navigating complex MAiD cases risk moral distress and uncertainty, and may inadvertently make decisions that are biased, narrow or ill-informed. The proposed Ethics Framework for MAiD includes a description of core values and principles relevant to the delivery of MAiD and a process guide to support the application of values and principles to cases. Use of the framework is illustrated through a simplified complex MAiD case. This Ethics Framework for MAiD is applicable to both clinical patient cases and organizational ethics issues, and adaptable to any jurisdiction and any legal or practice context. It may also be used by ethicists when conducting formal ethics case consultations involving MAiD. The goal of the paper is to empower MAiD assessors, providers, health professionals, program managers and ethicists to address ethical issues arising in everyday practice through the introduction of a pragmatic ethics framework specifically tailored to assisted dying.